2005
DOI: 10.1128/jb.187.8.2681-2692.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclic AMP-Regulated Genes in Mycobacterium tuberculosis Complex Bacteria under Low-Oxygen Conditions

Abstract: Mycobacterium tuberculosis is the etiological agent of tuberculosis (TB), which kills approximately 2 million people a year despite current treatment options. A greater understanding of the biology of this bacterium is needed to better combat TB disease. The M. tuberculosis genome encodes as many as 15 adenylate cyclases, suggesting that cyclic AMP (cAMP) has an important, yet overlooked, role in mycobacteria. This study examined the effect of exogenous cAMP on protein expression in Mycobacterium bovis BCG gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 63 publications
1
90
0
Order By: Relevance
“…It is postulated that secreted cAMP may prevent phagolysosome formation and thereby protect bacilli from host-mediated destruction (Lowrie et al, 1975(Lowrie et al, , 1979. Recently, it has been observed that exogenous cAMP induced the expression of several biologically significant genes in M. bovis BCG, thus implicating cAMPmediated regulation of gene expression as an important mechanism in the M. tuberculosis complex (Gazdik & McDonough, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that secreted cAMP may prevent phagolysosome formation and thereby protect bacilli from host-mediated destruction (Lowrie et al, 1975(Lowrie et al, , 1979. Recently, it has been observed that exogenous cAMP induced the expression of several biologically significant genes in M. bovis BCG, thus implicating cAMPmediated regulation of gene expression as an important mechanism in the M. tuberculosis complex (Gazdik & McDonough, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Complex effects of modulating cAMP levels in mycobacterium-infected macrophages have been described in many studies making it difficult to provide a simple model (e.g. Gazdik and McDonough, 2005;Yadav et al, 2004;Roach et al, 2005;Schorey and Cooper, 2003). It is even conceivable that mycobacteria can make and secrete cAMP into the phagosomal lumen, as suggested from earlier studies (Lowrie et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as a heat-shock protein, GroEL functions as a chaperonin to assist folding of linear amino acid chains into their respective three-dimensional structure (65). Cyclic-AMP-mediated up-regulation of GroEL2 under low-oxygen/CO 2 -enriched growth conditions was observed by Gazdik and McDonough (2005) (66). A previous study from our laboratory showed that GroEL2 promoter of MTB is highly active in M. smegmatis when subjected to different stress conditions including hypoxia (65).…”
Section: Validation Of Quantitative Proteomic Data By Qpcr-tomentioning
confidence: 99%